Application of FT near spectroscopy for determination of true protein and casein in milk - K. Šustová; J. Růžičková; J. Kuchtík (Czech Journal of Animal Science, 2007)
Our study deals with a possibility of determining true protein and casein in cow's, ewe's and goat's milk and in ewe's colostrums by FT NIR spectroscopy. Samples of milk were analysed by FT NIR in the reflectance mode with the transflectance cuvette. The values of correlation coefficients of calibration were as follows: cow's protein 0.943; cow's casein 0.964; ewe's protein 0.997; ewe's casein 0.977; goat's protein 0.989; goat's casein 0.890; ewe's colostrum protein 0.983. Calibration was tested using the same set of samples by the cross validation method. The values of correlation coefficients of validation were as follows: cow's protein 0.923; cow's casein 0.910; ewe's protein 0.994; ewe's casein 0.963; goat's protein 0.972; goat's casein 0.814; ewe's colostrum protein 0.871. The NIRS results were compared with reference data and no significant differences between them were found (P = 0.05). Results of this study indicate that FT NIR spectroscopy can be used for a rapid analysis of protein and casein in cow's, ewe's and goat's milk and ewe's colostrum.